L’affirmation d’une opposition française au « Lyon-Turin » : un conflit entre liminarité et intermédiarité - Kevin Sutton (Revue de Géographie Alpine)
Public interest enquiries conducted in relation to the proposed Lyon-Turin rail link have revealed the development of a composite protest to the project in France, particularly in 2012. Different associations have emerged, along with a personality, Daniel Ibanez, which have provided this protest movement with both a face and greater coherence in its opposition to the project. A somewhat argumentative stance in 2012-2013 has progressively given way to one that has more clearly denounced the project since 2014, a change indicating a form of liminality in the expression of conflict. The foundations of this opposition in France remain distinct from those in the Susa Valley, the historic area of opposition to the project in Italy. The principle of usefulness is foremost in France while, historically, the principle of responsibility has been the driving force in Italy. This article examines the paths of the different players making up French opposition to the project by analyzing the discourse and political underpinnings of the protagonists. The study’s comparative approach seeks to gain insights into the spatialities of the opposition movements in France and the Susa Valley. The article thus hopes to contribute to a more meaningful reflection on the distinction between “localness” and “proximity” by studying the relationship between protest movements and “mountain areas” as an entity in the process of the social construction of a line of argument.